Hydrothermal Synthesis of Nanodispersed Titanium Dioxide - Mizilevska, M.G.; Orenchyuk, O.Yu.; Sachko, V.M.; Tadeush, O.H.; Kotsyubynsky, V.O. (Physics and Chemistry of Solid State, 2016)
The paper is an overview of published data within the perspective method of hydrothermal synthesis of nanodispersed titanium dioxide. Organizing data allowed to capture the general trends of the relationships between the conditions of synthesis and structural morphological characteristics Nanodispersed titanium dioxide. Literature data are systematizated to select a universal method for revealing the relationship between the conditions of synthesis and structural, morphological properties of nanomaterials.